2012
DOI: 10.1104/pp.112.200089
|View full text |Cite
|
Sign up to set email alerts
|

Heat Reduces Nitric Oxide Production Required for Auxin-Mediated Gene Expression and Fate Determination in Tree Tobacco Guard Cell Protoplasts

Abstract: Tree tobacco (Nicotiana glauca) is an equatorial perennial with a high basal thermotolerance. Cultured tree tobacco guard cell protoplasts (GCPs) are useful for studying the effects of heat stress on fate-determining hormonal signaling. At lower temperatures (32°C or less), exogenous auxin (1-naphthalene acetic acid) and cytokinin (6-benzylaminopurine) cause GCPs to expand 20-to 30-fold, regenerate cell walls, dedifferentiate, reenter the cell cycle, and divide. At higher temperatures (34°C or greater), GCPs e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 83 publications
1
8
0
Order By: Relevance
“…Furthermore, the reduced NO levels in C. morifolium seedlings was followed by a sequence of events such as reduced S- nitrasoglutathione reductase (GSNOR) activity, accumulation of SNOs, an increase in peroxynitrites and consequently intensified protein tyrosine nitration (Chaki et al, 2011 ). Similarly, heat stress at 38°C for 16 h reduced NO accumulation in the guard cell protoplasts of tree Nicotiana glauca (Beard et al, 2012 ). Abolishing internal NO levels by the treatment with a well- known NO synthase (NOS) inhibitor, L-N(G)-nitroarginine methyl ester, also resulted in similar effects of heat stress in these cells.…”
Section: No In Connection With Heat Stressmentioning
confidence: 96%
See 1 more Smart Citation
“…Furthermore, the reduced NO levels in C. morifolium seedlings was followed by a sequence of events such as reduced S- nitrasoglutathione reductase (GSNOR) activity, accumulation of SNOs, an increase in peroxynitrites and consequently intensified protein tyrosine nitration (Chaki et al, 2011 ). Similarly, heat stress at 38°C for 16 h reduced NO accumulation in the guard cell protoplasts of tree Nicotiana glauca (Beard et al, 2012 ). Abolishing internal NO levels by the treatment with a well- known NO synthase (NOS) inhibitor, L-N(G)-nitroarginine methyl ester, also resulted in similar effects of heat stress in these cells.…”
Section: No In Connection With Heat Stressmentioning
confidence: 96%
“…Exogenous application of NO donors has also been able to reduce heat-induced cellular damage further underlining the involvement of NO in plant heat response (Song et al, 2006 ; Hasanuzzaman et al, 2013 ). Diverse cellular sites of NO synthesis have been documented previously under heat stress, mostly based on the fluorescent dyes such as 5,6- diaminofluorescein diacetate (Beard et al, 2012 ). For instance, heat stress induced NO-fluorescence was observed in diverse cell types in N. tabacum , including palisade mesophyll cells, all epidermal cell types, such as guard cells, subsidiary cells, long and short trichomes.…”
Section: No In Connection With Heat Stressmentioning
confidence: 99%
“…Protection methods to achieve high selectivity by preventing the interference of charged species (including anionic ascorbic acid, uric acid, neutral acetaminophen and cationic dopamine) were summarized. NO electrochemical sensors for detecting NO level in single cell 17, multi‐cell 21, kidney 22, 23, brain 24–26, heart 27, liver 28, 29, human blood serum samples 30, and plant cells 3133 were detailed. The trends for developing a novel NO sensor were outlooked in the last part.…”
Section: Introductionmentioning
confidence: 99%
“…Hasanuzzaman et al (2013) suggested that ABA may impart thermotolerance by raising the level of NO. On the contrary, heat inhibited NO accumulation in cultured guard cell protoplasts of Nicotiana glauca (tree tobacco) (Beard et al, 2012). Most probably the observed effects were related to the antioxidant action of NO, which elevates negative effects caused by the intensification of peroxidative metabolism under thermal stress .…”
Section: High Temperature Stressmentioning
confidence: 99%